Intangible ICT and Their Importance within Global Value Chains: An Empirical Analysis Based on Longitudinal Data Regression - Marek Pekarčík; Júlia Ďurčová; Jozef Glova (Mathematics, 2022)
The rising global importance of global value chains was enabled by developing information and communication technologies, ICT. A correct understanding of ICT roles determines a country’s global competitiveness. The study aims to examine the role of intangible ICT assets in creating domestic and foreign value added in export. Based on a sample of available longitudinal data from the EU-KLEMS database, for the period 2000–2015, 10 EU countries have been selected and analysed. We applied several panel regression models to confirm the important role of ICT capital, specific to intangible ICT, in creating domestic added value in exports and participation in the global value chains. Our results show that intangible ICT assets have a higher impact on the global value chain participation than tangible ICT assets. Moreover, the analysis at the sectoral level reveals a stronger effect of total ICT assets in the case of total business sectors.